Envelope Tracking RF Power Amplifiers: Fundamentals, Design Challenges, and Unique Opportunities Offered by LEES-SMART InGaAs-on-CMOS Process. (2016) - Ge, Tong; Guo, Linfei; He, Huiqiao; Yang, Kang; Jia, Yu; Chang, Joseph
Abstract: The RF power amplifier (PA) is often the most power dissipative block in a smartphone and it usually dissipates ∼50% of the total power. One major drawback of the envelop tracking (ET) PA is the limited (and insufficient) bandwidth of its supply modulator. The emerging LEES-SMART InGaAs-on-CMOS process offers a higher operation speed (due to the high speed InGaAs transistors) and the capability for complex signal processing. In this paper, we present the fundamentals and design challenges of ET PA, and how the emerging LEES-SMART InGaAs-on-CMOS process may be exploited for a high power-efficiency.